Preparation method and application of nanometer removable coating capable of isolating saliva pollution and improving bonding strength of zirconium oxide restoration

By preparing a nano-removable coating on the zirconia restoration, using a complex of tannic acid and ferric chloride hexahydrate, the problem of low bonding strength of zirconia ceramics and difficulty in isolating saliva contamination has been solved, achieving efficient Improved bonding strength and durability.

CN119326669AActive Publication Date: 2025-01-21SHANDONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411461090.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Zirconia ceramics have low bonding strength in oral restorations and are difficult to effectively isolate saliva contamination, affecting the bonding surface and resin adhesive, and reducing bonding strength and durability.

Method used

By preparing a nanometer on the surface of the oxidation repair body, the coating can be removed, and the natural polyphenol tannel (TA) and hexhexyxin iron chloride (FeCl3 · 6H2O) mathematically form a thin film coating of about 10nm. Salf pollution is removed and removed after bonding.

Benefits of technology

Effectively isolation of saliva pollution, improve the adhesion strength and durability of oxidative repair body, low cost, simple preparation method, and good coating biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326669A_ABST
    Figure CN119326669A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nanometer removable coating capable of isolating saliva pollution and improving the bonding strength of a zirconium oxide restoration. Comprising the following steps: (1) cleaning a substrate material; (2) preparing a tannic acid solution and a ferric trichloride hexahydrate solution; and (3) sequentially adding a ferric trichloride hexahydrate solution and a tannic acid solution into the cleaned substrate material, vortexing, adjusting the pH value, continuously vortexing, cleaning and drying to obtain the nano removable coating capable of isolating saliva pollution and improving the bonding strength of the zirconium oxide restoration. The MPN coating provided by the invention can effectively isolate interaction between protein and a substrate material zirconium oxide, overcomes saliva pollution caused by fitting of the restoration, and can be pre-coated before fitting and removed before clinical bonding, and meanwhile, the bonding durability of the zirconium oxide restoration treated by the MPN coating is close to that of the zirconium oxide restoration treated by cleaning, so that the bonding durability of the zirconium oxide restoration treated by the MPN coating is improved, and the service life of the zirconium oxide restoration treated by the MPN coating is prolonged. The zirconium oxide restoration body is superior to a zirconium oxide restoration body treated by an Ivoclean cleaning agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a nano removable coating which can isolate oral saliva, blood and other pollution and improve the bonding strength of a zirconia restoration, and belongs to the technical field of oral ceramic coatings. Background Art

[0002] In recent years, zirconia ceramics have been widely used in the production of various oral restorations, including full crowns, fixed bridges, bonded bridges, inlays, veneers, implant abutments, and orthodontic brackets, due to their excellent aesthetic properties, good biocompatibility, and ultra-high mechanical strength. However, unlike glass ceramics, the low bonding strength of zirconia has always been a major difficulty for dentists. First, because zirconia is a polycrystalline ceramic that does not contain a glass phase, it is difficult to be etched with hydrofluoric acid like glass ceramics; secondly, zirconia has high hardness and density, and the surface roughening method is limited, making it difficult to form a bonding surface that is micromechanically interlocked with the adhesive; finally, the chemical inertness of zirconia makes it difficult to form a chemical bond with organosilane.

[0003] At present, the more recognized treatment methods are sandblasting to increase the surface roughness of zirconium oxide, improve the mechanical retention of bonding, and use a resin bonding system containing phosphate monomers to form a chemical bond with the hydroxyl groups on the surface of zirconium oxide. In addition, moisture-proof and anti-fouling treatments must be done during clinical bonding, otherwise, the bonding strength of the restoration will be greatly reduced and the final durability will be affected. However, before the restoration is bonded, it must be tried in the mouth to check its suitability, which inevitably leads to the contamination of its bonding surface by various pollutants, including saliva, blood, gingival sulcus fluid, and silicone rubber indicators, among which saliva contamination has the greatest impact. 99% of saliva is water. In addition, it also contains various organic substances (such as salivary proteins, bacteria, food residues, and enzyme molecules) and inorganic components (minerals). During clinical trial wear, salivary proteins can form a nanofilm on the bonding surface of the restoration within seconds, reducing the free energy of the bonding surface and occupying the bonding sites between zirconium oxide and resin adhesives, affecting the penetration, curing and chemical bonding of the resin adhesive on the bonding surface, thereby reducing the bonding strength and durability of zirconium oxide. Scanning electron microscopy (SEM) revealed that a layer of protein film was visible on the surface of zirconium oxide contaminated by saliva. XPS elemental analysis of the bonding surface contaminated by saliva found that the surface C and N elements increased significantly, while the Zr element decreased. At the same time, the shear bonding strength (SBS) test found that the immediate bonding strength of zirconium oxide contaminated by saliva decreased significantly, and the decrease was more obvious after aging.

[0004] Therefore, domestic and foreign scholars have conducted a lot of research on how to remove the influence of saliva pollution on the bonding strength of zirconia. Existing methods mainly focus on surface physical treatment (sandblasting) and chemical cleaning. Among them, chemical cleaning mainly uses chemical cleaning agent Ivoclean (Ivoclean) to treat or clinical routine treatment alcohol wiping. Ivoclean (Ivoclean) is a purple strong alkaline supersaturated solution, the main components of which are spherical zirconia particles, sodium hydroxide, polyethylene glycol, water and pigments. Although this product can basically remove the influence of saliva pollution on the bonding of zirconia, the residual small zirconia particles will reduce the bonding durability. At the same time, the price of a single bottle of this product is nearly 500 yuan, and each bottle is only 5g, which has a high cost of use. And clinical routine treatment alcohol wiping cannot effectively remove the salivary protein film on the bonding surface and improve the bonding strength. The above methods focus on how to remove the influence of saliva pollution on the bonding strength of zirconia restorations after saliva pollution, and the purpose of the present invention is to find a simple, efficient and low-cost method to construct a protective barrier on the bonding surface of zirconia to fundamentally isolate saliva pollution. Therefore, there is an urgent need to develop a nano-removable coating material that can isolate saliva contamination and improve the bonding strength of zirconia restorations. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing and applying a nano-removable coating which can isolate saliva pollution and improve the bonding strength of a zirconia restoration.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a nano-removable coating that can isolate saliva pollution and improve the bonding strength of a zirconia restoration comprises the following steps:

[0008] (1) Clean the base material;

[0009] (2) preparing tannic acid (TA) solution and ferric chloride hexahydrate (FeCl3·6H2O) solution;

[0010] (3) Adding ferric chloride hexahydrate (FeCl3·6H2O) solution and tannic acid (TA) solution to the cleaned base material in sequence, vortexing for 20 to 60 seconds after each addition, adjusting the pH value to 7 to 9, and continuing to vortex for 20 to 60 seconds. After cleaning and drying, a nano-removable coating that can isolate saliva contamination and improve the bonding strength of zirconia restorations is obtained.

[0011] Preferably according to the present invention, in step (1), the base material is a zirconium oxide restoration.

[0012] Preferably, in step (1) of the present invention, the cleaning method is: adding anhydrous ethanol to the base material, ultrasonic cleaning for 10 minutes, then switching to deionized water, and continuing ultrasonic cleaning for 5 minutes.

[0013] Preferably according to the present invention, in step (2), the concentration of the tannic acid (TA) solution is 3-4 mg / mL.

[0014] Further preferably, the concentration of the tannic acid (TA) solution is 3.2 mg / mL.

[0015] Preferably according to the present invention, in step (2), the concentration of the ferric chloride hexahydrate (FeCl3·6H2O) solution is 0.75-1 mg / mL.

[0016] Further preferably, the concentration of the ferric chloride hexahydrate (FeCl3·6H2O) solution is 0.8 mg / mL.

[0017] Preferably, according to the present invention, in step (3), the volume ratio of the tannic acid (TA) solution to the ferric chloride hexahydrate (FeCl3·6H2O) solution is 1:1, and the mass concentration ratio is 4:1.

[0018] Preferably according to the present invention, in step (3), 0.1 M NaOH, pH=13 is used to adjust the pH.

[0019] The present invention also provides a nano-removable coating prepared by the above method, which can isolate saliva pollution and improve the bonding strength of the zirconium oxide restoration.

[0020] The above-mentioned nano-removable coating that can isolate saliva pollution and improve the bonding strength of zirconia restorations is used in oral restorations.

[0021] Preferably, according to the present invention, the application is specifically:

[0022] Before clinical trial wearing, a nano-removable coating that can isolate saliva pollution and improve the bonding strength of the zirconia restoration is prepared according to the above method to obtain a restoration pre-coated with an MPN (Fe-TA) coating;

[0023] The restorations pre-coated with MPN (Fe-TA) coating were tried in the oral cavity to check their fit;

[0024] After the clinical trial and before bonding, the restoration pre-coated with MPN (Fe-TA) coating was placed in HCl solution in vitro, ultrasonicated for 20-60s, and the pH value was adjusted to 1-2. It was then placed in NaOH solution to neutralize excess acid on the surface and remove residual protein. After cleaning and drying, the restoration with MPN (Fe-TA) coating removed was obtained and oral restoration was performed.

[0025] Further preferably, the concentration of the HCl solution is 0.1 mol / L, pH=1; the concentration of the NaOH solution is 0.1 mol / L, pH=13.

[0026] The technical features of the present invention are as follows:

[0027] The present invention uses a one-step assembly method to perform aqueous deposition on a zirconium oxide restoration using natural polyphenol tannic acid (TA) and a metal ion complex hexahydrate ferric chloride (FeCl3·6H2O) at room temperature, and can form a thin film coating of about 10nm within a few seconds. The thin film coating is initiated by polyphenol adsorption, inorganic cross-linking of metal ions, and guided by pH-dependent multivalent coordination bonding.

[0028] The specific mechanism of coating assembly and removal is as follows: when the pH is less than 2, the mixed solution is colorless, a large number of hydroxyl groups of TA (metal ion binding sites) are protonated at low pH, the Fe-TA cross-linking is unstable, it is a monohedral complex, and the membrane decomposes (coating removal mechanism); when the pH is greater than 3 and less than 6, the mixed solution is blue, Fe-TA is a dihedral complex, and the membrane is relatively unstable; when the pH is greater than 7, the mixed solution is red, Fe-TA is a trihedral complex, and the membrane has high stability and high mechanical properties (coating stabilization mechanism).

[0029] Natural polyphenol tannic acid (TA) is combined with salivary protein through hydrophobic interaction and hydrogen bonding. The present invention uses MPN (Fe-TA) coating as a barrier to effectively isolate the interaction between protein and zirconium oxide. Then, the pH dependence of the complex of natural polyphenol TA and trivalent Fe ions is utilized to immerse it in a hydrochloric acid solution. The nano coating degrades as the pH decreases. Then, the excess acid is neutralized by alkali and the residual protein is removed, thereby leaving a clean restoration surface for subsequent oral restoration.

[0030] The beneficial effects of the present invention are:

[0031] 1. The present invention utilizes natural polyphenol tannic acid (TA) and metal ion complex hexahydrate ferric chloride (FeCl3·6H2O) to prepare a nano-removable coating that can isolate saliva pollution and improve the bonding strength of zirconia restorations by assembling on a base material in one step. The MPN (Fe-TA) coating can effectively isolate the interaction between protein and zirconia, overcome the saliva pollution caused by the trial wearing of the restoration, and fundamentally eliminate the problem of saliva pollution affecting the bonding of zirconia. In addition, this MPN (Fe-TA) coating has good degradation performance, can be pre-coated before trial wearing, and removed before clinical bonding, and its effective performance can reach the effect of Ivoclean detergent. At the same time, the bonding durability of the zirconia restoration treated with the MPN (Fe-TA) coating is close to that of the zirconia restoration without saliva pollution, and is better than the zirconia restoration treated with Ivoclean detergent.

[0032] 2. The nano-removable coating provided by the present invention, which can isolate saliva pollution and improve the bonding strength of zirconia restorations, contains rich hydroxyl groups (metal ion chelators), which can reduce the activity of metal enzymes, extract metal ions required by microorganisms, and inhibit bacterial growth. At the same time, the polyphenolic groups of tannic acid (TA) can destroy the stability and integrity of cell membranes, and TA can reduce the activity of glucosyltransferase GTF (GTF can promote the adhesion of Streptococcus, the largest genus in the natural oral flora, to the tooth surface), thereby inhibiting bacterial adhesion and achieving an antibacterial effect.

[0033] 3. The raw material cost of the present invention is low, the preparation method is simple, and it is easier to promote quickly; the coating has good biocompatibility and is safe when tried in the oral cavity; the coating is thin and does not affect the placement of the restoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of saliva contamination and coating application during intraoral trial fitting of zirconia restorations.

[0035] Figure 2 The macroscopic color changes and scanning electron microscope observations of the zirconia ceramic block after sandblasting, the zirconia restoration pre-coated with MPN (Fe-TA) coating, and the zirconia restoration after removing the MPN (Fe-TA) coating;

[0036] Figure 2 Middle: A is a macroscopic color change diagram of the successful synthesis and removal process of the coating; B is a 5000x scanning electron microscope observation of the zirconia ceramic block after sandblasting; C is an electron microscope image magnified 5000 times after the MPN (Fe-TA) coating is prepared; D is an electron microscope image of the MPN (Fe-TA) coating magnified 20,000 times; E is a 5000x scanning electron microscope observation of the zirconia restoration with the MPN (Fe-TA) coating removed.

[0037] Figure 3 These are the Fourier transform infrared spectroscopy (FT-IR) test results of zirconia ceramic blocks after sandblasting, zirconia restorations pre-coated with MPN (Fe-TA) coating, and zirconia restorations with MPN (Fe-TA) coating removed.

[0038] Figure 4 These are the X-ray photoelectron spectrometer (XPS) surface element analysis results of zirconia ceramic blocks after sandblasting, zirconia restorations pre-coated with MPN (Fe-TA) coating, and zirconia restorations with MPN (Fe-TA) coating removed.

[0039] Figure 5 The results of water contact angle hydrophilicity test (WCA) of zirconia ceramic blocks after sandblasting, zirconia restorations pre-coated with MPN (Fe-TA) coating, and zirconia restorations after removing MPN (Fe-TA) coating.

[0040] Figure 6 The Fourier transform infrared spectroscopy (FT-IR) test results of zirconia restorations with MPN (Fe-TA) coating removed, zirconia restorations with MPN (Fe-TA) coating treated with saliva, zirconia restorations pre-coated with MPN (Fe-TA) coating, zirconia restorations treated with saliva, and zirconia ceramic blocks after sandblasting were presented.

[0041] Figure 7 Immunofluorescence analysis (BSA-FITC) of MPN (Fe-TA) coating sequestered proteins.

[0042] Figure 8 Antibacterial test results of MPN (Fe-TA) coating.

[0043] Fig. 9 This is the scanning electron microscope observation image of the MPN (Fe-TA) coating after antibacterial test.

[0044] Fig.10 The immediate bond strength results of different groups of zirconia restorations.

[0045] Fig.11 Shown are the aged bond strength results of different groups of zirconia restorations.

[0046] Fig.12 Shown are the fracture mode analysis results of different groups of zirconia restorations and typical scanning electron microscope images of the fracture surface.

[0047] Fig.13 Scanning electron microscope observations of different groups of zirconia restorations.

[0048] Fig.14 The X-ray photoelectron spectrometer (XPS) surface element analysis results of different groups of zirconia restorations. DETAILED DESCRIPTION

[0049] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0050] The raw materials and equipment used in the examples are all conventional commercially available products, and the saliva used is the saliva collected from normal healthy people on an empty stomach in the morning.

[0051] Example 1

[0052] A method for preparing a nano-removable coating that can isolate saliva pollution and improve the bonding strength of a zirconia restoration comprises the following steps:

[0053] (1) Place a sandblasted zirconia ceramic block with a size of 10 mm*10 mm*2 mm in a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, and ultrasonically clean it for 10 min. Then, replace it with 10 ml of deionized water and continue ultrasonicating for 5 min to obtain a thoroughly cleaned zirconia ceramic block;

[0054] (2) preparing a 3.2 mg / ml tannic acid (TA) solution and a 0.8 mg / ml ferric chloride hexahydrate (FeCl3·6H2O) solution;

[0055] (3) After the pretreated zirconia ceramic block was dried, it was placed in a 50-ml centrifuge tube, and 10 ml of FeCl3·6H2O solution and 10 ml of TA solution were added in sequence. After each addition, vortexing was performed for 60 seconds. Subsequently, 1.5 ml of 0.1 M NaOH solution was added to the centrifuge tube to adjust the pH value of the mixed solution from 2.5 to 8. The mixture was vortexed for another 60 seconds. After cleaning and drying, a nano-removable coating (MPN (Fe-TA) coating) was obtained, which could isolate saliva contamination and improve the bonding strength of zirconia restorations.

[0056] Example 2

[0057] A method for preparing a nano-removable coating that can isolate saliva pollution and improve the bonding strength of a zirconia restoration comprises the following steps:

[0058] (1) Place a sandblasted zirconia ceramic block with a size of 10 mm*10 mm*2 mm in a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, and ultrasonically clean it for 10 min. Then, replace it with 10 ml of deionized water and continue ultrasonicating for 5 min to obtain a pretreated zirconia ceramic block;

[0059] (2) preparing a 3 mg / ml tannic acid (TA) solution and a 0.5 mg / ml ferric chloride hexahydrate (FeCl3·6H2O) solution;

[0060] (3) After the pretreated zirconia ceramic block was dried, it was placed in a 50-ml centrifuge tube, and 10 ml of FeCl3·6H2O solution and 10 ml of TA solution were added in sequence. After each addition, vortexing was performed for 40 seconds. Subsequently, 1.5 ml of 0.1 M NaOH solution was added to the centrifuge tube to adjust the pH value to 8. The tube was vortexed for another 40 seconds. After cleaning and drying, a nano-coating that can isolate saliva contamination and improve bonding strength was obtained.

[0061] Example 3

[0062] A method for preparing a nano-removable coating that can isolate saliva pollution and improve the bonding strength of a zirconia restoration comprises the following steps:

[0063] (1) Place a sandblasted zirconia ceramic block with a size of 10 mm*10 mm*2 mm in a 50 ml centrifuge tube, add 10 ml of anhydrous ethanol, and ultrasonically clean it for 10 min. Then, replace it with 10 ml of deionized water and continue ultrasonicating for 5 min to obtain a pretreated zirconia ceramic block;

[0064] (2) preparing a 4 mg / ml tannic acid (TA) solution and a 1 mg / ml ferric chloride hexahydrate (FeCl3·6H2O) solution;

[0065] (3) After the pretreated zirconia ceramic block was dried, it was placed in a 50-ml centrifuge tube, and 10 ml of FeCl3·6H2O solution and 10 ml of TA solution were added in sequence. After each addition, vortexing was performed for 20 seconds. Subsequently, 1.5 ml of 0.1 M NaOH solution was added to the centrifuge tube to adjust the pH value to 8. The tube was vortexed for another 20 seconds. After cleaning and drying, the color of the zirconia ceramic block changed from white to purple, and a nano-coating was obtained that could isolate saliva contamination and improve bonding strength.

[0066] Example 4

[0067] Schematic diagram of saliva contamination and coating application of zirconia restorations during intraoral trial fitting Figure 1 As shown, this embodiment simulates saliva contamination during intra-oral trial wearing.

[0068] A nano-removable coating that can isolate saliva pollution and improve the bonding strength of the zirconia restoration is prepared according to the method described in Example 1 to obtain a zirconia restoration pre-coated with an MPN (Fe-TA) coating;

[0069] The zirconia restoration pre-coated with MPN (Fe-TA) coating was placed in a 50 ml centrifuge tube, 10 ml of freshly collected saliva was added, and the porcelain block was immersed for 60 seconds, and then rinsed with water and dried to obtain the MPN (Fe-TA) coated zirconia restoration after saliva treatment;

[0070] The MPN (Fe-TA) coated zirconia restoration after saliva treatment was placed in a 50ml centrifuge tube, added with 10ml of 0.1mol / L, pH=1 HCl solution, ultrasonicated for 60s, and then washed with water to remove HCl. Subsequently, it was placed in a 0.1M, pH=13 NaOH solution to neutralize excess acid and remove residual protein. Finally, it was washed and dried to obtain the zirconia restoration with the MPN (Fe-TA) coating removed, which was recorded as the coating group (coating pre-coating group).

[0071] Comparative Example 1

[0072] A sandblasted zirconia ceramic block with a size of 10mm*10mm*2mm was placed in a 50ml centrifuge tube, and then 10ml of anhydrous ethanol was added and ultrasonic cleaning was performed for 10min. Then 10ml of deionized water was used and ultrasonic cleaning was continued for 5min to obtain a thoroughly cleaned zirconia restoration, which was recorded as the zirconia cleaning group (cleaning group).

[0073] Comparative Example 2

[0074] A sandblasted zirconia ceramic block with a size of 10mm*10mm*2mm was placed in a 50ml centrifuge tube, and 10ml of freshly collected saliva was added to immerse the ceramic block for 60s. The block was then rinsed and dried with water to obtain a saliva-treated zirconia restoration, which was recorded as the saliva contamination group.

[0075] Comparative Example 3

[0076] The sandblasted zirconia ceramic block with the size of 10mm*10mm*2mm was placed in a 50ml centrifuge tube, and then 10ml of anhydrous ethanol was added, and ultrasonic cleaning was performed for 10min, and then 10ml of deionized water was used, and ultrasonic cleaning was continued for 5min to obtain a thoroughly cleaned zirconia restoration. After rinsing and drying, it was immersed in 10ml of freshly collected saliva for 60s, then taken out, rinsed and dried, and wiped with an alcohol cotton ball containing 75% alcohol commonly used in clinical practice to obtain a zirconia restoration wiped with an alcohol cotton ball, which was recorded as the alcohol wiping group.

[0077] Comparative Example 4

[0078] The sandblasted zirconia ceramic block with the size of 10mm*10mm*2mm was placed in a 50ml centrifuge tube, and then 10ml of anhydrous ethanol was added, and ultrasonic cleaning was performed for 10min, and then 10ml of deionized water was used, and ultrasonic cleaning was continued for 5min to obtain a thoroughly cleaned zirconia restoration. After rinsing and drying, it was immersed in 10ml of freshly collected saliva for 60s, then taken out, rinsed and dried, and cleaned with a commercial chemical cleaner Ivoclean. According to the instructions, a small brush was used to evenly apply the purple liquid on the bonding surface for 20s, and then rinsed with water for 40s and dried to obtain the zirconia restoration cleaned with Ivoclean, which was recorded as the commercial cleaner Ivoclean group (Ivoclean group).

[0079] Test Example 1

[0080] 1. Macroscopic color observation and scanning electron microscopy observation were performed on the sandblasted zirconia ceramic block (size 10 mm*10 mm*2 mm), the zirconia restoration pre-coated with MPN (Fe-TA) coating described in Example 4 (zirconia-MPN), and the zirconia restoration with MPN (Fe-TA) coating removed described in Example 4 (zirconia-MPN-saliva-HCl-NaOH). The results are as follows: Figure 2 As shown in A to E.

[0081] Depend on Figure 2 A shows that after the MPN (Fe-TA) coating is successfully synthesized, the color of the zirconia ceramic block changes from white to purple; after the MPN (Fe-TA) coating is removed, the color of the zirconia ceramic block changes from purple back to white.

[0082] Depend on Figure 2 From B to E, it can be seen that the surface of zirconia is pit-shaped after sandblasting. After coating with MPN (Fe-TA) coating, the surface becomes relatively flat. After magnification, film deposition and MPN (Fe-TA) aggregates can be seen. After the MPN (Fe-TA) coating is removed, the surface can be seen to return to the pit shape.

[0083] 2. Fourier transform infrared spectroscopy (FT-IR) tests were performed on the sandblasted zirconia ceramic block (size 10 mm*10 mm*2 mm), the zirconia restoration pre-coated with MPN (Fe-TA) coating described in Example 4 (zirconia-MPN), and the zirconia restoration with MPN (Fe-TA) coating removed described in Example 4 (zirconia-MPN-saliva-HCl-NaOH). The results are as follows: Figure 3 shown.

[0084] Depend on Figure 3 It can be seen that the infrared characterization of the zirconia ceramic block after being coated with MPN (Fe-TA) coating was found at a wavelength of 2983.67 cm -1 The absorption peak of tannic acid phenolic hydroxyl group can be seen at the top, indicating that the MPN (Fe-TA) coating is successfully applied. The absorption peak disappears after the coating is removed, which is the same as cleaning the zirconia ceramic block.

[0085] 3. X-ray photoelectron spectrometer (XPS) surface element analysis was performed on the sandblasted zirconia ceramic block (size 10 mm*10 mm*2 mm), the zirconia restoration pre-coated with MPN (Fe-TA) coating described in Example 4 (zirconia-MPN), and the zirconia restoration with MPN (Fe-TA) coating removed described in Example 4 (zirconia-MPN-saliva-HCl-NaOH). The results are as follows: Figure 4 shown.

[0086] Depend on Figure 4 It can be seen that after the coating is applied, the C1s element on the surface increases (the coating contains TA), the Zr3d element decreases significantly (the coating covers the surface of the zirconia ceramic block), and the Fe2p element appears (the coating contains Fe), all of which indicate that the MPN (Fe-TA) coating is successfully coated. After the coating is removed, the surface element content is similar to that of the zirconia ceramic block, indicating that the coating has been successfully removed.

[0087] 4. The water contact angle hydrophilicity test (WCA) was performed on the sandblasted zirconia ceramic block (size 10mm*10mm*2mm), the zirconia restoration pre-coated with MPN (Fe-TA) coating described in Example 4 (zirconia-MPN), and the zirconia restoration with MPN (Fe-TA) coating removed described in Example 4 (zirconia-MPN-saliva-HCl-NaOH). The results are as follows: Figure 5 shown.

[0088] Depend on Figure 5 It can be seen that the average static water contact angle of the zirconia ceramic block surface after sandblasting is 47.94°, the average static water contact angle of the zirconia restoration surface pre-coated with MPN (Fe-TA) coating (zirconia-MPN) is 29.77°, and the average static water contact angle of the zirconia restoration surface after removing the MPN (Fe-TA) coating (zirconia-MPN-saliva-HCL-NaOH) is 48.41°.

[0089] Test Example 2

[0090] 1. The zirconia restoration with the MPN (Fe-TA) coating removed described in Example 4 (zirconia-MPN-saliva-HCl-NaOH), the zirconia restoration with MPN (Fe-TA) coating treated with saliva described in Example 4 (zirconia-MPN-saliva), the zirconia restoration pre-coated with MPN (Fe-TA) coating described in Example 4 (zirconia-MPN), the zirconia restoration treated with saliva described in Comparative Example 2 (zirconia-saliva) and the zirconia ceramic block (size 10 mm*10 mm*2 mm) after sandblasting described in Comparative Example 1 were tested by Fourier transform infrared spectroscopy (FT-IR). The results are as follows: Figure 6 shown.

[0091] Depend on Figure 6 It can be seen that the zirconia porcelain block contaminated by saliva is at 1394.08cm -1 An absorption peak can be seen at , where CN represents the abundant amide band in salivary protein, which is used as the absorption peak of salivary protein. After the zirconium oxide is coated, it is immersed in saliva and then removed by acid, and the absorption peak is not detected on the surface, which shows that there is no protein adsorption on the surface.

[0092] 2. The zirconia restoration (zirconia-MPN-BSA-HCL-NaOH) with the MPN (Fe-TA) coating removed described in Example 4 and the zirconia ceramic block (size 10 mm*10 mm*2 mm) after sandblasting described in Comparative Example 1 were subjected to a bovine serum albumin immunofluorescence test (BSA-FITC). The results are as follows: Figure 7 shown.

[0093] Depend on Figure 7It can be seen that after the zirconium oxide was immersed in calf serum albumin immunofluorescence labeling, the surface fluorescence signal was strong, while after the MPN (Fe-TA) coating group was immersed in protein and then the coating was removed, almost no fluorescence signal was seen on the surface. It can be seen that the MPN (Fe-TA) coating can effectively isolate protein contamination.

[0094] Test Example 3

[0095] 1. The antibacterial function of the zirconia restorations in the coating group of Example 4 and the cleaning group of Comparative Example 1 was tested, and the antibacterial rate of the coating was calculated by plate colony count: Common oral bacteria-Streptococcus mutans was selected as the model bacteria for the antibacterial test. It was cultured at 37°C in a constant temperature anaerobically (80% N2, 10% N2 and 10% CO2), revived and purified, and 1*10 4 CFU / ml bacterial suspension is ready for use. The zirconium oxide specimens before and after coating preparation are irradiated with UV light on both sides for 40 minutes each (n=3), placed in a 24-well culture plate, and 100μl of the above bacterial suspension is added to the surface of each sample, and anaerobically incubated for 4 hours. Subsequently, 1ml of BHI liquid culture medium is added to each sample well, and anaerobic culture is continued for 24 hours. The sample is taken out and gently shaken and rinsed with sterile PBS buffer to remove suspended bacteria on the surface of the sample. The sample is then placed in a sterile centrifuge tube filled with PBS, ultrasonicated for 60 seconds, and then vortexed for 3 minutes to fully shake the bacteria on the surface of the sample into PBS. Then the bacterial suspension is diluted 100 times, 100μl is drawn onto a sterile solid agar medium, and a disposable sterile applicator is evenly applied. It is anaerobically cultured at 37°C for 24 hours, and then the number of colonies on each culture medium is counted.

[0096] The antibacterial rate of the coating is calculated according to the following formula:

[0097] (AR): AR = (AB) / A * 100%, where A is the average colony count of clean zirconia and B is the average colony count of the coating group. The results are as follows Figure 8 shown.

[0098] The zirconia restorations of the coating group of Example 4 and the cleaning group of Comparative Example 1 were anaerobically co-cultured with Streptococcus mutans, and then observed by scanning electron microscopy. The results are as follows: Fig. 9 shown.

[0099] Depend on Figure 8It can be seen that the MPN (Fe-TA) coating has a significant antibacterial effect, with an antibacterial rate of up to 66.4%. This is because the tannic acid TA in the MPN (Fe-TA) coating contains abundant hydroxyl groups (metal ion chelators), which can reduce the activity of metal enzymes, extract metal ions required by microorganisms, and inhibit bacterial growth; at the same time, the polyphenolic groups of TA can destroy the stability and integrity of the cell membrane; most importantly, TA can reduce the activity of glucosyltransferase GTF (GTF can promote the adhesion of Streptococcus, the largest genus in the natural oral flora, to the tooth surface), thereby inhibiting bacterial adhesion and achieving an antibacterial effect.

[0100] Depend on Fig. 9 It can be seen that a large number of mutans streptococci can be seen in the cleaning group, while the number of pre-coating is relatively reduced. After magnification, it can be seen that the bacteria on the surface of the coating group are splitting and the cell membrane is deformed. This shows that the coating group can achieve antibacterial effects by inhibiting bacterial adhesion and destroying the stability of bacterial cell membranes.

[0101] 2. The bonding strength of the zirconia restorations in the coating group of Example 4, the cleaning group of Comparative Example 1, the saliva contamination group of Comparative Example 2, the alcohol wiping group of Comparative Example 3, and the Ivoclean group of Comparative Example 4 was tested. The specific method is: a zirconia restoration bonding specimen (clinical resin bonding system) was prepared in vitro, and a hot and cold cycler (the specimen was immersed in 55°C and 5°C, and the cycle was repeated 10,000 times, and each immersion was 20 seconds) to simulate the long-term (1 year) aging condition of oral use. The immediate bonding strength, aged bonding strength and fracture strength of the above five groups of zirconia restorations were measured using a universal testing machine, and the sample size was n=10.

[0102] The immediate bonding strength results of the above five groups of zirconia restorations are as follows Fig.10 The aged bond strength results are shown in Fig.11 The fracture mode results are shown in Fig.12 shown.

[0103] Depend on Fig.10 It can be seen that the average immediate bonding strength of the saliva contamination group was 5.72MPa, the average immediate bonding strength of the alcohol wiping group was 7.275MPa, the average immediate bonding strength of the Ivoclean group was 14.717MPa, and the average immediate bonding strength of the coating group was 14.772MPa, indicating that the cleaning effect of the coating group was basically the same as that of the Ivoclean group and the cleaning group.

[0104] Depend on Fig.11It can be seen that after aging, the average aging bond strength of the cleaning group was 11.19MPa, the average aging bond strength of the saliva contamination group was 2.078MPa, the average aging bond strength of the alcohol wiping group was 3.4MPa, the average aging bond strength of the Ivoclean group was 7.9789MPa, and the average aging bond strength of the coating group was 10.802MPa. This shows that aging affects the bonding strength of zirconia, among which the chemical cleaning agent group has poor durability, and the coating group has superior effect.

[0105] Depend on Fig.12 It can be seen that in the immediate bonding fracture mode, the cleaning group, the chemical cleaning group and the MPN (Fe-TA) coating group were mainly mixed fractures, while the saliva contamination group and the alcohol wiping group were mainly bonding fractures. After aging, all groups were mainly bonding fractures (bonding fracture: fracture occurred between the resin adhesive and the ceramic interface; cohesive fracture: fracture occurred inside the resin adhesive, and the ceramic surface was covered by the resin adhesive; mixed fracture: both occurred, and the ceramic surface was partially covered by the resin adhesive). Scanning electron microscopy observed that there was no resin adhesive on the surface of the bonding fractured ceramic, and after magnification, a pit-like structure after sandblasting could be seen, while the resin adhesive and primer residues could be seen on the surface of the mixed fracture, and some of them were pit-like morphologies of zirconia after sandblasting.

[0106] 3. Scanning electron microscopy and X-ray photoelectron spectroscopy (XPS) surface element analysis were performed on the zirconia restorations of the coating group of Example 4, the cleaning group of Comparative Example 1, the saliva contamination group of Comparative Example 2, the alcohol wiping group of Comparative Example 3, and the Ivoclean group of Comparative Example 4. The results are as follows: Figures 13-14 shown.

[0107] Depend on Fig.13 It can be seen that the surface of zirconium oxide is uneven after sandblasting, and a layer of protein film can be seen on the surface after salivary protein adsorption. There is no obvious change on the surface after alcohol wiping. After Ivoclean chemical cleaning, the surface recovers the pit-like morphology similar to the cleaning group, but small zirconium oxide particles can be seen remaining. The MPN (Fe-TA) coating group has pit-like results on the surface, which is the same as the cleaning group. This shows that the chemical cleaning Ivoclean group can effectively remove saliva pollution, and the coating group has the same effect.

[0108] Depend on Fig.14 It can be seen that the carbon content on the surface of zirconia increased significantly after saliva contamination, and the nitrogen content also increased significantly; there was no obvious change after alcohol wiping; the carbon content on the surface of the chemical cleaning agent Ivoclean group decreased significantly, and the nitrogen content was basically undetectable, but the zirconium content was slightly higher than the cleaning group; the surface element analysis results of the coating group were similar to those of the cleaning group. This shows that the chemical cleaning agent Ivoclean can effectively remove saliva contamination from the surface of zirconia restorations, but small zirconia particles will remain, while the coating group can isolate saliva contamination without residue.

Claims

1. A method for preparing a nano-removable coating that can isolate saliva pollution and improve the bonding strength of zirconia restorations, characterized in that: The steps include: (1) Clean the base material; (2) preparing tannic acid solution and ferric chloride hexahydrate solution; (3) Adding ferric chloride hexahydrate solution and tannic acid solution to the cleaned base material in sequence, vortexing for 20 to 60 seconds after each addition, adjusting the pH value to 7 to 9, and continuing to vortex for 20 to 60 seconds. After cleaning and drying, a nano-removable coating is obtained that can isolate saliva contamination and improve the bonding strength of the zirconia restoration.

2. The preparation method according to claim 1, characterized in that In step (1), the base material is a zirconium oxide restoration.

3. The preparation method according to claim 1, characterized in that: In step (1), the cleaning method is: adding anhydrous ethanol to the base material, ultrasonic cleaning for 10 minutes, then switching to deionized water, and continuing ultrasonic cleaning for 5 minutes.

4. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the tannic acid solution is 3-4 mg / mL; Further preferably, the concentration of the tannic acid solution is 3.2 mg / mL.

5. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the ferric chloride hexahydrate solution is 0.75-1 mg / mL; Further preferably, the concentration of the ferric chloride hexahydrate solution is 0.8 mg / mL.

6. The preparation method according to claim 1, characterized in that: In step (3), the volume ratio of the tannic acid solution to the ferric chloride hexahydrate solution is 1:1, and the mass concentration ratio is 4:

1.

7. A nano-removable coating that can isolate saliva pollution and improve the bonding strength of zirconia restorations, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 6.

8. Use of the nano-removable coating according to claim 1 that can isolate saliva pollution and improve the bonding strength of zirconia restorations in oral restorations.

9. The use according to claim 8, characterized in that The application is specifically: Before clinical trial wearing, a nano-removable coating capable of isolating saliva contamination and improving the bonding strength of a zirconia restoration is prepared according to the method of claim 1 to obtain a restoration pre-coated with an MPN coating; The restorations pre-coated with MPN coating were tried in the mouth to check their fit; After the clinical trial and before bonding, the restoration pre-coated with MPN coating was placed in HCl solution in vitro, ultrasonicated for 20-60s, the pH value was adjusted to 1-2, and then placed in NaOH solution to neutralize excess acid on the surface and remove residual protein. After cleaning and drying, the restoration with MPN coating removed was obtained and oral restoration was performed.

Citation Information

Patent Citations

  • Application and preparation method of alkaline coating on surface of dental zirconia ceramic

    CN105147525A

  • Method for adhering and combining zirconia prosthesis and natural tooth

    CN108658628A

  • Zirconia ceramic bonding surface modification method for enhancing bonding capacity

    CN115141038A

  • Retardation film-forming composition, method for producing retardation film and retardation plate

    KR1020240072041A

  • Wireless transmitter of operating signal for warning lamp

    KR102466966B1